PRINCIPLES OF LAW AND EQUALITY BEFORE THE LAW IN THE RUSSIAN CRIMINAL LAW - Konstantin V. Chemerinsky (Современная наука и инновации, 2022)
The article discusses the contents of the two principles of criminal law, the principle of legality and the principle of equality before the law, reveal their essence and meaning.